The ability of the prognostic nutritional index to predict short-term mortality in geriatric acute heart failure - Hilal Akça; Hatice Şeyma Akça; Abuzer Özkan; Serdar Özdemir (The Egyptian Heart Journal)
Abstract Background Heart failure is a critical cardiovascular condition, necessitating comprehensive treatment approaches and contributing to elevated mortality rates. This study aimed to evaluate the effect of the prognostic nutritional index (PNI) on the prognosis of geriatric patients diagnosed with acute heart failure. Results A total of 104 patients were included and evaluated retrospectively in this study; 57.7% of them were females, and 19.24% of the patients died. A statistically significant difference was identified between high (≥ 35.6) and low PNI (< 35.6) groups in terms of lymphocyte count, neutrophil–lymphocyte ratio, C-reactive protein, and albumin (p values: < 0.001, < 0.001, 0.011, and < 0.001, respectively). The area under the curve (AUC) value for albumin was 0.53 (95% CI: 0.30–0.83) with a cutoff value of 3.1 g/dL; for lymphocyte count, it was 0.61 (95% CI: 0.57–0.84) with a cutoff value of 0.34 × 103/µL; and for PNI, it was 0.58 (95% CI: 41.18–85.06) with a cutoff value of 34.6. Conclusion The low PNI group exhibited a significantly higher mortality rate; nonetheless, PNI alone does not hold clinical significance as a prognostic marker. However, when combined with other clinical parameters, it can contribute to a more comprehensive assessment of patients.